Fast fixed-time synchronization of T–S fuzzy complex networks - Liu, Shuai; Zhao, Lingli; Zhang, Wanli; Yang, Xinsong; Alsaadi, Fuad E. (Nonlinear Analysis: Modelling and Control, 2021)
In this paper, fast fixed-time (FDT) synchronization of T–S fuzzy (TSF) complex networks (CNs) is considered. The given control schemes can make the CNs synchronize with the given isolated system more fleetly than the most of existing results. By constructing comparison system and applying new analytical techniques, sufficient conditions are established to derive fast FDT synchronization speedily. In order to give some comparisons, FDT synchronization of the considered CNs is also presented by designing FDT fuzzy controller. Numerical examples are given to illustrate our new results.
Keywords: fixed-time synchronization; complex networks; T–S fuzzy systems; T–S fuzzy control